2022
DOI: 10.1002/cdt3.18
|View full text |Cite
|
Sign up to set email alerts
|

Current status and progress in immunotherapy for malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare and aggressive malignant disease. Currently, the platinum doublet of pemetrexed and cisplatin is the standard first‐line treatment for unresectable MPM. However, recent promising results of immunotherapy have markedly changed the landscape of MPM treatment. Further, the ongoing innovative therapeutic strategies are expected to expand the range of treatment options; however, several questions remain unanswered. First, establishing predictive biomarkers with high po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In 2020, a combination of anti-PD-1 mAb nivolumab plus anti-CTLA-4 mAb ipilimumab was approved by the U.S. Food and Drug Administration (FDA) as a first-line therapy for unresectable MPM (7,15,16). Whereas initial promising results of mAb-based therapy have changed the landscape of MPM treatment, the efficacy is limited to a certain subset of patients, indicating an urgent need to establish biomarkers for patient selection (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a combination of anti-PD-1 mAb nivolumab plus anti-CTLA-4 mAb ipilimumab was approved by the U.S. Food and Drug Administration (FDA) as a first-line therapy for unresectable MPM (7,15,16). Whereas initial promising results of mAb-based therapy have changed the landscape of MPM treatment, the efficacy is limited to a certain subset of patients, indicating an urgent need to establish biomarkers for patient selection (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are limited clinical treatment options available for this disease. One promising option is a combination therapy involving pemetrexed and cisplatin, which has been shown to improve response rate, overall survival, and quality of life in mesothelioma patients [ 125 ]. However, it is essential to note that many patients treated with this therapy experience tumor progression or recurrence within a year [ 125 ].…”
Section: Application Strategies Of Natural Anticancer Peptides and Pr...mentioning
confidence: 99%
“…One promising option is a combination therapy involving pemetrexed and cisplatin, which has been shown to improve response rate, overall survival, and quality of life in mesothelioma patients [ 125 ]. However, it is essential to note that many patients treated with this therapy experience tumor progression or recurrence within a year [ 125 ]. Recent studies have shown that a sialic acid-binding lectin isolated from Rana catesbeiana oocytes has the potential as an anticancer agent.…”
Section: Application Strategies Of Natural Anticancer Peptides and Pr...mentioning
confidence: 99%
“…Cisplatin was the first metal-based chemotherapeutic drug approved by Food and Drug Administration (FDA) in 1978 [ 1 , 2 , 3 ] and even today it is administered alone or in combination with radiotherapy or other antineoplastic agents for the treatment of several cancers, such as testicular [ 4 ], ovarian [ 5 ], lung [ 6 ], esophageal [ 7 ], stomach [ 8 ], prostate [ 9 ], cervical [ 10 ], colorectal cancers [ 11 ], head–neck carcinoma [ 12 ], non-Hodgkin lymphoma [ 13 ], multiple myeloma [ 14 ], melanoma [ 15 ] and mesothelioma [ 16 ].…”
Section: Introductionmentioning
confidence: 99%